Peroxisomal monoubiquitinated PEX5 interacts with the AAA ATPases PEX1 and PEX6 and is unfolded during its dislocation into the cytosol - Pedrosa, AG (2018)
PEX1 and PEX6 are two members of the ATPases associated with diverse cellular activities (AAA) family and the core components of the receptor export module of the peroxisomal matrix protein import machinery. Their role is to extract monoubiquitinated PEX5, the peroxisomal protein-shuttling receptor, from the peroxisomal membrane docking/translocation module (DTM), so that a new cycle of protein transportation can start. Recent data have shown that PEX1 and PEX6 form a heterohexameric complex that unfolds substrates by processive threading. However, whether the natural substrate of the PEX1-PEX6 complex is monoubiquitinated PEX5 (Ub-PEX5) itself or some Ub-PEX5-interacting component(s) of the DTM remains unknown. In this work, we used an established cell-free in vitro system coupled with photoaffinity cross-linking and protein PEGylation assays to address this problem. We provide evidence suggesting that DTM-embedded Ub-PEX5 interacts directly with both PEX1 and PEX6 through its ubiquitin moiety and that the PEX5 polypeptide chain is globally unfolded during the ATP-dependent extraction event. These findings strongly suggest that DTM-embedded Ub-PEX5 is a bona fide substrate of the PEX1-PEX6 complex.